Extending records of albinism and skin disorders in American cownose rays to southeastern Brazil - Rodrigues, Alexandre [UNESP]; Shkola, Wesley; Rangel, Bianca S. (Wiley, 2023)
Albinism is a genetic condition expressed as a lack of integumentary and retinal melanin. Although documented across many vertebrate species, albinism and other skin disorders are rarely observed in elasmobranchs (sharks and rays). The present study describes the first confirmed case of albinism in American cownose ray (Rhinoptera bonasus), and three other juveniles of the species with undetermined skin disorders observed in São Paulo, southeastern Brazil. Pigmentation disorders have already been observed in American cownose rays from the North Atlantic, including two cases of leucism and a possible albinism. Based on the results, it was discussed the possible consequences of albinism for the ray survival as well as the possible causes for the undetermined skin disorders.
Keywords: colour pigmentation; elasmobranch; field observation; Rhinoptera bonasus; white cownose ray